KONDISI KIMIA TANAH PADA LAHAN AGROFORESTRI DAN KEBUN CAMPURAN DI NGATA KATUVUA DONGI-DONGI KECAMATAN PALOLO KABUPATEN SIGI SULAWESI TENGAH - Andi, .; Wardah, .; Toknok, Bau (Universitas Tadulako, 2018)
This study aims to determine the soil chemical properties in cacao agroforestry and cacao mixed garden. The research was conducted for three months, October – December, 2017, at Ngata Katuvua Dongi-Dongi, Palolo Sub-district, Sigi District, Central Sulawesi. The study used a survey method, soil samples collected on five points at 0-30cm and 30-60cm depth for each plot, and then compiled into one sample. The soil samples collection are 4 soil sample. The soil samples were analyzed at the Laboratory of Soil Science Unit of the Faculty of Agriculture, Tadulako University. The study results showed that soil chemical properties on cacao agroforestry tend to be better than soil on cacao mixed garden. The Soil chemical properties on cacao agroforestry: pH 6.42, N-total 0.27%, P-available 13.79ppm, K-available 0.26 (cmol (+) kg-1, C-organic 3.69% and CEC 22,34 (cmol (+) kg-1. While the soil chemical properties on the cacao mixed garden: pH 6.20, N-total 0.11%, P-available 6.67ppm, K-available 0.12 (cmol (+) kg-1, C-organic 1.84%, and CEC 13.45 (cmol (+) kg-1.Keywords: soil chemistry, agroforestry, mixed garden.